2022
DOI: 10.1186/s12891-022-05166-3
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of early application of pelvic circumferential compression device to reduce bleeding in pelvic fractures

Abstract: Background To study of efficacy of early pelvic circumferential compression device using in patients with suspected pelvic trauma, compared with conventional stepwise approach. Methods Traumatic injury and at least one of the following criteria are required for inclusion: loss of consciousness or a Glasgow coma score (GCS) of less than 13; systolic blood pressure less than 90 mmHg; falling from more than 6 m; injury to several important organs; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Historic cases in whom PCCD was applied after clinical or radiological confirmation of a pelvic fracture served as control [ 18 ]. Rungsinaporn et al who also assessed blood saving effects from early PCCD application in the ER, showed that PCCD on patients suspicious of pelvic injury lead to considerably lower number of pRBC transfusions in the early PCCD group compared to historic controls where PCCD was only applied after radiological confirmation of the pelvic fracture [ 19 ]. This advantage could be due to a time difference of approx.…”
Section: Discussionmentioning
confidence: 99%
“…Historic cases in whom PCCD was applied after clinical or radiological confirmation of a pelvic fracture served as control [ 18 ]. Rungsinaporn et al who also assessed blood saving effects from early PCCD application in the ER, showed that PCCD on patients suspicious of pelvic injury lead to considerably lower number of pRBC transfusions in the early PCCD group compared to historic controls where PCCD was only applied after radiological confirmation of the pelvic fracture [ 19 ]. This advantage could be due to a time difference of approx.…”
Section: Discussionmentioning
confidence: 99%
“…30 External mechanical compression devices are being applied empirically in the prehospital environment and trauma bay successfully, reducing the number of blood transfusions necessary during resuscitation without increasing the risk of complication. 31,32 If patients remain hemodynamically unstable despite EMC application, other strategies for controlling hemorrhage should be used early. These include angiography and embolization, extraperitoneal pelvic packing, [33][34][35] and/or application of external fixation devices.…”
Section: Management Of the Pelvic Ring In The Multiple-injury Patientmentioning
confidence: 99%
“…Given that the EMC provides circumferential compression, it may be better than an anteriorly based external fixator or a C-clamp in managing pelvic hemorrhage, which can only provide compression in a single plane 30 . External mechanical compression devices are being applied empirically in the prehospital environment and trauma bay successfully, reducing the number of blood transfusions necessary during resuscitation without increasing the risk of complication 31,32 …”
Section: Management Of the Pelvic Ring In The Multiple-injury Patientmentioning
confidence: 99%
“…1 Measures, such as pelvic binders, have been proven to reduce rate of blood transfusion and mortality rate. 2,3 Another technique, resuscitative endovascular balloon occlusion of the aorta (REBOA) has shown promise although knowledge about its practice patterns are limited. 4,5 Angioembolisation for the management of pelvic haemorrhage was performed as early as 1972.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, there have been vast improvements in hospital protocols for the management of major pelvic trauma, with angiography fast becoming a vital component 1 . Measures, such as pelvic binders, have been proven to reduce rate of blood transfusion and mortality rate 2,3 . Another technique, resuscitative endovascular balloon occlusion of the aorta (REBOA) has shown promise although knowledge about its practice patterns are limited 4,5 .…”
Section: Introductionmentioning
confidence: 99%